Peran Manajemen Komite Madrasah Dalam Meningkatkan Mutu Pelayanan Pendidikan di MI Ma’arif 1 Bumi Mulya dan MIN 1 Way Kanan - nur, Nurhasanah; Fakhri, Jamal; romlah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The quality of educational services is one of the main indicators of the success of educational institutions, including madrasahs, in carrying out their functions as providers of formal education based on Islamic values. In the context of educational decentralization and the implementation of madrasah-based management, the Madrasah Committee has a strategic role as a working partner that supports the achievement of educational goals through involvement in the planning, implementation, evaluation, and supervision of educational programs. This study aims to comprehensively examine how the role of the Madrasah Committee management can contribute to improving the quality of educational services in two Islamic elementary educational institutions, namely MI Ma'arif 1 Bumi Mulya and MIN 1 Way Kanan, which are located in Way Kanan Regency, Lampung Province. This study uses a qualitative approach with a descriptive method. The results of the study indicate that the Madrasah Committee in both madrasahs has a significant role in supporting the improvement of the quality of education services. These roles include the function of providing consideration in strategic decision-making, mobilizing financial and non-financial support, liaison between the madrasah and parents/guardians of students, and as a supervisory body for the implementation of learning activities. Supporting factors for the success of the committee's role include good communication between the madrasah and the committee, high commitment from the committee administrators, and the openness of the madrasah in involving the committee in various aspects of policy. However, there are still obstacles such as budget constraints, lack of management training for committee members, and minimal active participation of some members. This study recommends ongoing training and coaching for Madrasah Committee members as well as more supportive policies from local governments and the Ministry of Religion to strengthen the institutional role of the committee in the madrasah education system. With good management, the madrasah committee can become a major actor in encouraging the transformation of the quality of education services based on community participation.